Phylogenetic Diversity, Distribution, and Cophylogeny of Giant Bacteria (Epulopiscium) with their Surgeonfish Hosts in the Red Sea - Miyake, Sou; Ngugi, David K.; Stingl, Ulrich (Frontiers in Microbiology, 2016)
Epulopiscium is a group of giant bacteria found in high abundance in intestinal tracts of herbivorous surgeonfish. Despite their peculiarly large cell size (can be up to 600 µm), extreme polyploidy (some with over 100,000 genome copies per cell) and viviparity (whereby mother cells produce live offspring), details about their diversity, distribution or their role in the host gut are lacking. Previous studies have highlighted the existence of morphologically distinct Epulopiscium cell types (defined as morphotypes A to J) in surgeonfish genera, but the corresponding genetic diversity and distribution among other surgeonfishes remain mostly unknown. Therefore, we investigated the phylogenetic diversity of Epulopiscium, distribution and co-occurrence in multiple unrelated hosts. Here, we identified eleven new phylogenetic clades, six of which were also morphologically characterized. Three of these novel clades were phylogenetically and morphologically similar to cigar-shaped type A1 cells, found in a wide range of surgeonfishes including Acanthurus nigrofuscus, while three were similar to smaller, rod-shaped type E that has not been phylogenetically classified thus far. Our results also confirmed that biogeography appears to have relatively little influence on Epulopiscium diversity, as clades found in the Great Barrier Reef (GBR) and Hawaii were also recovered from the Red Sea. Although multiple symbiont clades inhabited a given species of host surgeonfish and multiple host species possessed a given symbiont clade, statistical analysis of host and symbiont phylogenies indicated significant cophylogeny, which in turn suggests co-evolutionary relationships. A cluster analysis of Epulopiscium sequences from previously published amplicon sequencing dataset revealed a similar pattern, where specific clades were consistently found in high abundance amongst closely related surgeonfishes. Differences in abundance may indicate specialization of clades to certain gut environments reflected by inferred differences in the host diets. Overall, our analysis identified a large phylogenetic diversity of Epulopiscium (up to 10% sequence divergence of 16S rRNA genes), which lets us hypothesize that there are multiple species that are spread across guts of different host species.